Struggles in the WTO's dispute settlement procedures: focused on the US power dominance. (5th December 2016) - Kwon, Youngmin
Abstract : Purpose: The purpose of this paper is to investigate differences among member groups, with more detailed division of groups than the existing literatures, during the WTO's dispute settlement procedures. Design/methodology/approach: Trade disputes requested through the WTO's DSU regimes up until 2011 were statistically described and analyzed using logit regression models. Findings: Despite capacity gaps, developing nations have encountered stronger legal challenges from the US and, although without much capacity gaps, similar patterns of litigation rivalries between the US and other advanced countries, with the exception of the EU, have been also found during dispute settlements in the WTO regimes. Research limitations/implications: Although the DSU procedures themselves might not be biased for/against certain member groups, there has been some evidence of the struggles of weaker opponent groups of the US during the actual litigation processes. Originality/value: Power dominances of the US against developing nations as well as developed nations, other than the EU, have been neglected in many previous researches on the topic with a simple developed-developing dichotomy classification.